(untitled) - Wallace, Linda K. (Chicago, 2004)
This book provides focus and options in planning, promoting, and developing or expanding a library. Establishing a library with furnishings, staff, and services does little good if its mission and promotion of that mission are not carefully considered, just as a clear vision of service is useless if the institution cannot meet its goals
Keywords: Libraries,Mission statements.,Library planning.,Libraries,Thư viện,Nhiệm vụ,Lập kế hoạch cho thư viện,Thư viện; Aims and objectives.,Marketing.,Mục tiêu và nhiệm vụ,Tiếp thị